2007
DOI: 10.1093/aje/kwm127
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Urate and Risk of Parkinson's Disease

Abstract: Oxidative stress contributes to dopaminergic neuron degeneration in Parkinson's disease. Urate, a potent antioxidant, could be neuroprotective. To determine whether higher plasma concentrations of urate predict a reduced risk of Parkinson's disease, the authors conducted a nested case-control study among participants in the Health Professionals Follow-up Study, a cohort comprising over 18,000 men who provided blood samples in 1993-1995. Eighty-four incident cases of Parkinson's disease were diagnosed through 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
283
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(304 citation statements)
references
References 36 publications
9
283
1
4
Order By: Relevance
“…This study observed no interaction between serum uric acid levels and smoking [661]. A metaanalysis of these three prospective studies yielded a RR of 0.80 (95% CI 0.71-0.90) per 1.32 mg/dl increase in serum uric acid concentration (corresponding to 1 standard deviation in the Health Professionals Follow-up Study) [661].…”
Section: Uric Acid and Goutmentioning
confidence: 52%
See 2 more Smart Citations
“…This study observed no interaction between serum uric acid levels and smoking [661]. A metaanalysis of these three prospective studies yielded a RR of 0.80 (95% CI 0.71-0.90) per 1.32 mg/dl increase in serum uric acid concentration (corresponding to 1 standard deviation in the Health Professionals Follow-up Study) [661].…”
Section: Uric Acid and Goutmentioning
confidence: 52%
“…The inverse association was stronger in non-smokers than smokers [659].The Rotterdam study also found lower PD risk with increasing baseline serum uric acid (p for trend 0.04), but no interaction by smoking status or gender [660]. Similarly, a case-control study nested within the Health Professionals Follow-up Study of men reported an inverse association between baseline serum uric acid and PD (RR 0.43, 95% CI 0.18-1.02 for highest versus lowest quartile of serum uric acid, p for trend 0.017) [661]. The association was stronger when cases with serum uric acid measurement within 4 years prior to PD diagnosis were excluded (RR 0.17, 95% CI 0.04-0.69 for highest versus lowest quartile of serum uric acid).…”
Section: Uric Acid and Goutmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on the case–control studies, subjects with increased levels of serum UA and gout were associated with a decreased risk for developing PD (Weisskopf, O'Reilly, Chen, Schwarzschild, & Ascherio, 2007), although in one study, the plasma UA levels in women were not significantly associated with the risk of PD (O'Reilly et al., 2010). Based on a prospective population study, higher levels of serum UA were also associated with a decreased risk of PD (Chen, Mosley, Alonso, & Huang, 2009; de Lau, Koudstaal, Hofman, & Breteler, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In longitudinal cohort studies, urate levels correlate with risk of developing PD later in life, with higher levels being associated with reduced disease risk [13][14][15][16][17]. History of gout is associated with reduced risk of developing either PD [48] or Alzheimer's disease [21].…”
Section: Urate and Its Determinants Are A Risk Factor For Neurodegenementioning
confidence: 99%